2013
DOI: 10.3390/soc3010128
|View full text |Cite
|
Sign up to set email alerts
|

Culture Matters: Individualism vs. Collectivism in Conflict Decision-Making

Abstract: Does culture matter in decision-making? Existing literature largely assumes that the cognitive processes that inform decision-making are universally applicable, while only very few studies indicate that cultural norms and values shape cognitive processes. Using survey based quasi-experimental design, this research shows that subjects with higher levels of individualism tend to be more rational in their decision processing, while those with higher levels of collectivism tend to be more dependent and less likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 48 publications
0
33
0
2
Order By: Relevance
“…Our reflection supported the suggestion that bi-lingual community members, who are respected in their communities, are well placed to form a connection between their communities and local health services. 6,7,8,9 Our reflection confirmed that, due to their understanding of local cultural values and mores 10 , they were trusted and were, therefore, able to more effectively assist community members to gain access to health services and resources, often spending several more hours than the paid allocated 11 hours per week.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Our reflection supported the suggestion that bi-lingual community members, who are respected in their communities, are well placed to form a connection between their communities and local health services. 6,7,8,9 Our reflection confirmed that, due to their understanding of local cultural values and mores 10 , they were trusted and were, therefore, able to more effectively assist community members to gain access to health services and resources, often spending several more hours than the paid allocated 11 hours per week.…”
Section: Discussionmentioning
confidence: 52%
“…Revised Manuscript-FEB 2014 reduced and shared while the success of the role would be enhanced as also supported in LeFebvre et al9 with regards to non-Caucasian communities' modus operandi being one of collectivism. A similar cyclical apprentice mentoring model or 'buddy system' has been implemented in Melbourne and is showing evidence of durability.12 Investment in the development of a community-based learning culture may have been less costly and more effective in that information would be disseminated more widely.…”
mentioning
confidence: 73%
“…Thus, this cultural norm informed this study's participants to regard caregiving to their relatives as a principal socio-cultural obligation. This is apparent in the following quotes: The cultural orientation of Ghana towards the female gender also assigns the caring role for homes, children and sick relatives specifically to mothers and older daughters [38][39][40]. Hence, some participants who were women also voiced out that it was culturally expected of them as mothers and older daughters to take care of ill family members such as women with advanced breast cancer as illustrated in the quote below: "Hmmm..!…”
Section: Plos Onementioning
confidence: 99%
“…105 The enforcement of collectivist norms has been shown to shape cognitive processes during intergroup conflict and periods of ethnonational violence. 106 Work by Albert Bandura reveals that retaliation for…”
Section: Revisiting the ''Culture Turn'' In Foreign Policy Analysis: mentioning
confidence: 99%